Implication of Apnea‐Hypopnea Index, a Measure of Obstructive Sleep Apnea Severity, for Atrial Fibrillation in Patients With Hypertrophic Cardiomyopathy - Xu, Haobo (J Am Heart Assoc, 2020)
BACKGROUND: Obstructive sleep apnea (OSA) is common and independently associated with atrial fibrillation (AF) in patients with hypertrophic cardiomyopathy (HCM). This study aimed to investigate the relationship between apnea‐hypopnea index (AHI), a measure of OSA severity, and prevalence of AF in a large series of patients with HCM. METHODS AND RESULTS: A total of 555 patients with HCM who underwent sleep evaluations were retrospectively included. Data from polysomnography studies, echocardiography, and baseline clinical characteristics were collected. OSA was present in 327 patients (58.9%). Patients with OSA or higher AHI quartiles were older, more often male, had a higher body mass index, and more clinical comorbidities. The prevalence of AF increased in patients with OSA (23.9% versus 13.6%, P=0.003) or across AHI quartiles (9.4%, 17.3%, 26.6%, and 25.2%, respectively; P for trend <0.001). After adjustment for age, sex, body mass index, New York Heart Association class, left atrial diameter, hypertension, oxygen desaturation index, and obstructive HCM, highest AHI quartile (odds ratio, 4.42; 95% CI, 1.35–14.52 [P=0.014]) or moderate to severe OSA (odds ratio, 3.03; 95% CI, 1.28–7.20 [P=0.012]) but not presence of OSA (odds ratio, 1.58; 95% CI, 0.84–2.97 [P=0.153]) were significantly associated with AF. Higher AHI levels were also factors associated with persistent or permanent AF (highest AHI quartile with odds ratio, 10.96; 95% CI, 1.07–111.85). CONCLUSIONS: Severity of AHI level is independently associated with AF in patients with HCM. Clinical trials are required to determine the benefits of OSA treatment on AF in patients with HCM.